Perencanaan Model Drainase Berpori Untuk Meminimalisir Terjadinya Genangan Air Di Perumahan New Golden Hills Blok I - Eryan, Enol; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Program Studi Teknik Sipil Universitas Bosowa, 2024)
This study aims to obtain: (1) the dimensions of the drainage channel cross-section with the presence of pores, (2) the infiltration discharge with the presence of pores in the drainage, and (3) the flow discharge with the presence of pores in the drainage channel. This study took place in the New Golden Hills Housing Block I, which is located in the Manggala Village, Manggala District, Makassar City, South Sulawesi Province. Data collection techniques were carried out by direct observation, in managing data using descriptive qualitative methods, namely the method of calculation and elaboration of the results of processing field data from the location being reviewed. The results of research with the presence of pores as follows; with a distance of 2 meters between pores along the channel, it is proven that it can affect the flow rate, where before the pores, the flow rate is 1.0249 m3/second, and after the pores the flow is 1.0245 m3/second. Where the flow rate in the main channel 1 is 0.3610 m3/second, the infiltration discharge in the main channel 2 is 0.2995 m3/second, and the infiltration discharge in the main channel 3 is 0.3640 m3/second. However, with the presence of pores, it does not have much effect on the dimensions of the drainage channel.